2007
DOI: 10.1523/jneurosci.0668-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin: Is 2 Better than 1?: Table 1.

Abstract: Editor's Note: These short reviews of a recent paper in the Journal, written exclusively by graduate students or postdoctoral fellows, are intended to mimic the journal clubs that exist in your own departments or institutions. For more information on the format and purpose of the Journal Club, please see http://www.jneurosci.org/misc/ifa_features.shtml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…We observed that SDF-1-mRFP1-containing vesicles situated in close proximity to CXCR4-EGFP-expressing cells in the SGZ frequently stained with antibodies against synaptotagmin-1, synaptoporin, or SV2, which are all known to be associated with transmittercontaining synaptic vesicles (Jinno and Kosaka, 2003;Khanna et al, 2007;Leitzell, 2007) (Fig. 4).…”
Section: Resultsmentioning
confidence: 95%
“…We observed that SDF-1-mRFP1-containing vesicles situated in close proximity to CXCR4-EGFP-expressing cells in the SGZ frequently stained with antibodies against synaptotagmin-1, synaptoporin, or SV2, which are all known to be associated with transmittercontaining synaptic vesicles (Jinno and Kosaka, 2003;Khanna et al, 2007;Leitzell, 2007) (Fig. 4).…”
Section: Resultsmentioning
confidence: 95%
“…8a ). Of note, the SYT1 protein level, which is the homolog of SYT2 and the most studied member of the synaptotagmin family 46 , 48 , 49 , remained unchanged (Fig. 8a ).…”
Section: Resultsmentioning
confidence: 98%
“…4). Synaptotagmin1 is a multifunctional substrate that acts as calcium sensor in the Ca 2+ ‐dependent release of neurotransmitter vesicles (Leitzell, 2007) and in the regulation of synaptic vesicle docking and recycling (Fukuda et al, 2000; Llinas et al, 2004). Because synaptotagmin1 is an abundant synaptic vesicle protein and is expressed throughout the brain, it has also been used as a marker to estimate the number of synapse boutons in the CNS.…”
Section: Discussionmentioning
confidence: 99%